Preliminary observation on lethal salinity and ph of catfish [Pangasius sutchi fowler) larvae - Mohammad Mohsin, A. K. (Malaysian Society of Applied Biology, 1985)
Pangasius sutchi, locally known as ikan patin is imported from 'Thailand at varying sizes, and is cultured in Malaysian ponds. Recently Jabatan Perikanan, Malacca was successful in the induced breeding of the species. 'This faculty took initiative to conduct further experiment and to find out suitable parameters for culturing the species. The aim of this paper is to find the lethal salinity and pH doses on the larvae.